Community Empowerment Strategy Through the Development of Tourism Villages Based on Local Potential - Martin Hanabean (CV. Sutan Mandiri Sejahtera, 2026)
The background of this research is based on the importance of optimizing regional potential to reduce poverty and urbanization in rural West Java. The main objective of the study is to analyze community empowerment strategies through the development of tourism villages based on local potential and to formulate a sustainability model. This research used a descriptive qualitative method with a case study approach in Selasari Tourism Village, Parigi District, Pangandaran Regency. Data were collected through in-depth interviews, participant observation, and documentation with the Tourism Awareness Group (Pokdarwis) and local MSMEs. The results indicate that a structured empowerment strategy through the stages of awareness (awakening), capacity building (enabling), and empowerment was able to optimize the potential of the Santirah River karst and Sundanese cultural wisdom into high-value special interest tourism commodities. This success was supported by harmonious and transparent governance synergy between Pokdarwis, BUMDes, and the Village Government in implementing a one-stop financial management system. The conclusion of this study confirms that a community-based tourism approach has been proven to significantly increase household income, create new jobs, grow women's micro, small, and medium enterprises (MSMEs), reduce youth urbanization, and simultaneously revitalize the commitment to nature conservation and local cultural preservation independently.